A Critical Reflection on the Studies of the Use of Social Media in the Organization - Meisam Samband; Ali Akbar Farhangi; Farnoush Zangouei (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
By describing online tools, social media provides a channel for transmitting or sharing information with wide audiences. These media target the organization's socialization by involving human factors in an organization's procedural and existential philosophy. Investigating the research conducted on the relationship between social media and organizational communication mainly induces a one-sided and positive attitude towards these media to the audience. The dominant theoretical discourse in the organizational field is that the use of social media is necessary and developmental because influencing organizational communication helps organizations to create a space for dialogue and interpersonal communication as well as attract the participation of stakeholders. But the main point is that empirical evidence in the field of social media and organizational communication is largely dependent on the case and cannot be generalized. Therefore, in this article, with a critical reflection, while reviewing the role of social media in the socialization of the organization, the positivist view of organizational researchers towards these media has been discussed. The results of the studies show that the positive effects of social media on organizations have been magnified and, as portrayed, are not necessarily beneficial to human factors and organizations.